Experience of pediatric palliative care among children with cancer in a tertiary care hospital in Bangladesh - Rahman, M. Shaidur; Urmy, Sabikun Naher; Newaz, Moshrefa; Islam, M. Atiqul; Khan, Tasnuva; Khatun, Habiba; Simi, Maliha Alam (International Journal of Contemporary Pediatrics, 2024)
Background: Palliative care is a holistic approach which can improve patients and their family’s quality of life through the prevention and relief of physical symptoms as well as support for emotional, social and spiritual suffering. Despite the substantial need for palliative care there is very limited access in Bangladesh, with only a few palliative care services focused on children including several hospital-based services as well as home and hospice-based services, within the capital city of Dhaka. The aim of the study was to evaluate the effect of pediatric palliative care on quality of life in children with cancer. Methods: This was an institutional based descriptive study conducted in the department of pediatric hematology and oncology and pediatric palliative care unit, Dhaka medical college hospital, Dhaka, from May to August 2023. A total of thirty child and parent pairs were taken as the study population according to inclusion and exclusion criteria. Outcome was evaluated by the CPOS-2 questionnaires for symptom and Lanskys performance status scale for assessment of activity level. Results: The median age of the children were 5.7 years where 70.0% were male. The duration of disease of the patients was up to 6 months in 63.3% cases. One third of the patients had ALL, 13.3% had NHL, and 10.0% had Ewing sarcoma while another 10.0% having neuroblastoma. Conclusions: There is significant improvement in the quality of life of pediatric cancer patients and their parents, as well as the enhanced performance status of patients with cancer after receiving pediatric palliative care.